Development of Reflection Card-Based Counseling Media for Positive Islamic Body Image - Tuti Ameliah Rambe; Ramadhan Lubis (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Negative body image among adolescents has increasingly emerged alongside the influence of social media, which promotes diverse standards of beauty and ideal appearance. This condition may lead to low self-confidence, poor self-acceptance, and limited social interaction among students. This study aims to develop counseling media based on reflection cards to foster positive body image within the framework of Islamic values. Employing a Research and Development (R&D) approach with the 4D model limited to three stages Define, Design, and Develop the research involved 30 students in the needs analysis, one material expert, one media expert, one counseling teacher, and nine students in a limited trial. Data were collected through interviews and questionnaires, and analyzed using descriptive quantitative and qualitative techniques. The results show that the reflection card media achieved a feasibility level of 96% from the media expert and 98% from the material expert, categorized as highly feasible. Student responses reached 88.3%, while counseling teacher responses were 98%, both categorized as highly practical. These findings indicate that reflection card-based counseling media is feasible and practical for supporting the development of positive body image among students in accordance with Islamic perspectives.